Development of Dual Power Multirotor System. (30th July 2017) - Lin, Chin E.; Supsukbaworn, Thanakorn
Abstract : Vertical take-off and landing (VTOL) aircraft has good flight characteristics and system performance without runway. The multirotor system has been tried to expand into larger size for longer endurance or higher payload. But the motor power to endurance ratio has been limited. Due to the specific energy of gasoline being much higher than battery, introducing gasoline engine into multirotor system can be considered. This paper proposes a dual power multirotor system to combine a quadrotor using gasoline engines to provide major lift in shorter arm with another quadrotor using brushless DC motors to offer most controllable force with longer arm. System design, fabrication, and verification of the proposed dual power multirotor system development are presented. Preliminary flights have achieved 16 kg payload for long endurance flight. This is useful for various applications with advanced improvements.